2008
DOI: 10.1002/adma.200702005
|View full text |Cite
|
Sign up to set email alerts
|

Nanopatterned Self‐Assembled Monolayers by Using Diblock Copolymer Micelles as Nanometer‐Scale Adsorption and Etch Masks

Abstract: Nanopatterned self‐assembled monolayers (SAMs) are obtained from a simple, straight‐forward procedure by using masks derived from monolayers of block copolymer micelles. The nanopatterned SAMs consist of regularly spaced circular hydrophilic areas with diameters of approximately 60 nm on a continous hydrobhopic background or vice versa. The surfaces are shown to be excellent tools for the preparation of arrays of nanocrystals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…The substrate of a silicon wafer was treated with oxygen plasma to remove any organic impurities and to increase the surface hydroxyl concentration. Subsequent exposure of the treated Si substrate to tricholorovinylsilane vapor produces covalently bound vinyl groups on the surface 15. The pretreated substrate was then subjected to the iCVD process.…”
Section: Methodsmentioning
confidence: 99%
“…The substrate of a silicon wafer was treated with oxygen plasma to remove any organic impurities and to increase the surface hydroxyl concentration. Subsequent exposure of the treated Si substrate to tricholorovinylsilane vapor produces covalently bound vinyl groups on the surface 15. The pretreated substrate was then subjected to the iCVD process.…”
Section: Methodsmentioning
confidence: 99%
“…The complete spatial and orientational control of these nanoscopic patterns was dependent on the solvent quality, polymer concentration, and molecular weight of either or both blocks [33]. Hence, spin coating of the PS-b-P4VP spherical inverse micelles from toluene onto different substrate surfaces produced a quasi-hexagonal nanopattern preferably sustaining the micelle sizes [34,35]. The nearly monodisperse Ag NPs stabilized by BCP micelle films were previously synthesized from Ag salt-encapsulated PS-b-P4VP micelles in toluene [23,36].…”
Section: Resultsmentioning
confidence: 97%
“…As the amphiphilic block copolymers are consist of hydrophilic and hydrophobic chains which are covalently linked together, they can self-assembled into either regular or reverse micelles or other nanostructures in selective solvents which are mainly depending on the molecular structures of polymers and the polarity of solvents [26]. For example, the regular micelles with hydrophobic cores and hydrophilic corona can be exclusively formed by dissolution of block copolymers in heating polar solvents [25] while the reverse micelles with reverse constructions are able to be formed with the introduction of nonpolar solvents [27]. Meanwhile, it has been reported that P4VP can function as a ligand to coordinate with metal ions due to the existence of the pyridyl groups [14].…”
Section: Resultsmentioning
confidence: 99%